2014
DOI: 10.1007/s10482-014-0274-5
|View full text |Cite
|
Sign up to set email alerts
|

Functional expression of a novel alkaline-adapted lipase of Bacillus amyloliquefaciens from stinky tofu brine and development of immobilized enzyme for biodiesel production

Abstract: Using enrichment procedures, a lipolytic strain was isolated from a stinky tofu brine and was identified as Bacillus amyloliquefaciens (named B. amyloliquefaciens Nsic-8) by morphological, physiological, biochemical tests and 16S rDNA sequence analysis. Meanwhile, the key enzyme gene (named lip BA) involved in ester metabolism was obtained from Nsic-8 with the assistance of homology analysis. The novel gene has an open reading frame of 645 bp, and encodes a 214-amino-acid lipase (LipBA). The deduced amino acid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 33 publications
1
17
2
Order By: Relevance
“…After incubation in 100% n-hexane, Est7 retained 83.8% of the activity in the absence of organic solvent, which indicated that Est7 had good stability in both hydrophilic and hydrophobic organic solvents. In particular, compared with other reports, Est7 showed higher stability than rEstSL3 [30] and LipBA45 [31] in organic solvents. These features are good prerequisites for the application of this enzyme in biocatalytic reactions.…”
Section: Enzyme Characterization Of Purified Esterase Est7contrasting
confidence: 52%
“…After incubation in 100% n-hexane, Est7 retained 83.8% of the activity in the absence of organic solvent, which indicated that Est7 had good stability in both hydrophilic and hydrophobic organic solvents. In particular, compared with other reports, Est7 showed higher stability than rEstSL3 [30] and LipBA45 [31] in organic solvents. These features are good prerequisites for the application of this enzyme in biocatalytic reactions.…”
Section: Enzyme Characterization Of Purified Esterase Est7contrasting
confidence: 52%
“…produce various fungicidal agents, amylases, hyaluronic acid, and plasmin, which not only play an important role in fermentation, but also confer a health effect on humans (Zhao et al, 2009;He et al, 2013). Several studies have suggested that the growth of Bacillus cereus is inhibited by the presence of LAB because of the acidic environment created as a result of the increased growth of LAB (Cai et al, 2014). Bacilli did not constitute a major microbiota in grasshopper sub shrimp paste, but their effect on the flavor and nutrition of grasshopper sub shrimp paste and the interaction between Bacilli and LAB require further study (Gu et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Due to the rigid regulation of lipase synthesis, the cloning of lipase genes is often preferred. The first documentation of lipase gene from B. amyloliquefaciens cloning and application in biodiesel production was reported by Cai et al [61]. B. amyloliquefaciens Nsic-8 lipase gene, lipBA, was isolated from a stinky tofu brine and successfully cloned in E. coli.…”
Section: Discussionmentioning
confidence: 99%